1990
DOI: 10.1111/j.1365-2621.1990.tb03563.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transitions of Salt‐soluble Proteins from Pre‐ and Postrigor Chicken Muscles

Abstract: Salt-soluble protein (SSP) was extracted from pre-and postrigor chicken muscles at various pH values, and protein thermal denaturation was studied using several techniques. Heating at l"C/min from 20 to 70°C induced a three-to fourfold increase in breast and leg hydrophobic@. Differential scanning calorimetry of breast and leg SSP showed a major transition occurring within the range 55 to 64°C with the value dependent on rigor state and pH. Protein-protein association, as measured by turbidity change upon heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

1992
1992
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 20 publications
8
36
0
Order By: Relevance
“…In the second phase, T4 showed a slight increase in G′ from 45℃ to 50℃ and T1, T2 and T3 from 45℃ to 52℃. The similar result has been reported by Xiong and Brekke (1990), who found that gelation was initiated at 45 − 50℃ being dependent upon the proteinprotein interaction. Then all treatments showed a decline until 55℃ was reached which resulted from denaturation of Control: 100% pork leg meat (PLM); T1: 25% chicken breast meat (CBM) and 75% PLM; T2: 50% CBM and 50% PLM; T3: 75% CBM and 25% PLM; T4: 100% CBM.…”
Section: Resultssupporting
confidence: 77%
“…In the second phase, T4 showed a slight increase in G′ from 45℃ to 50℃ and T1, T2 and T3 from 45℃ to 52℃. The similar result has been reported by Xiong and Brekke (1990), who found that gelation was initiated at 45 − 50℃ being dependent upon the proteinprotein interaction. Then all treatments showed a decline until 55℃ was reached which resulted from denaturation of Control: 100% pork leg meat (PLM); T1: 25% chicken breast meat (CBM) and 75% PLM; T2: 50% CBM and 50% PLM; T3: 75% CBM and 25% PLM; T4: 100% CBM.…”
Section: Resultssupporting
confidence: 77%
“…T1 had typical dynamic rheological curve of raw pork batters (Kang et al, 2014b). When heated from 20 °C to 41 °C, G' decreased slowly, and then at a slightly increase from 41 °C to 50 °C, because the meat protein denaturation occurred, and gelation at 45-50 °C was initiated after protein-protein interaction had taken place (Xiong & Brekke;1990). Due to the denaturation of the myosin tails, and this changes could disruption of the protein network that had previously formed at lower temperatures, G' had a moderate decline from 53 °C to 56 °C (Wu et al, 2009b;Álvarez et al, 2012).…”
Section: Dynamic Rheological Measurementmentioning
confidence: 99%
“…Solution pH has been shown to affect thermally induced protein-protein aggregation and transition temperatures (Goodno and Swenson, 1975b;Ziegler and Acton, 1984;Morita et al, 1987;Xiong and Brekke, 1990). Ziegler and Acton (1984), also using light scattering techniques on bovine natural actomyosin, found two distinct transitions at 43.0 and 56.O"C for pH 5.50, and 48.5 and 57.5"C for pH 6.00.…”
mentioning
confidence: 97%